2018
DOI: 10.3390/su10051649
|View full text |Cite
|
Sign up to set email alerts
|

Role of Creative Industries as a Regional Growth Factor

Abstract: The purpose of this study is to evaluate the impact of employment in creative industries on the regional and national economic growth of Ecuador. The methodology used is a panel econometric model in which the temporary and structural dimensions considered to meet the proposed objective are addressed. The inputs of a basic production function were considered and the influence of creative employment was estimated as a proxy indicator of the work factor and of tax collections as a proxy of the capital factor on r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 34 publications
1
19
0
2
Order By: Relevance
“…Howkins [58] also argued that the creative economy reflects exploitation of the economic value of creative activities by individuals who develop their imagination, i.e., the intellectual human capital that is the condition of the creative industries. Recently, Correa-Quezada et al [59] clarified that these industries have a significant influence on local/regional development.…”
Section: Creativity In Citiesmentioning
confidence: 99%
“…Howkins [58] also argued that the creative economy reflects exploitation of the economic value of creative activities by individuals who develop their imagination, i.e., the intellectual human capital that is the condition of the creative industries. Recently, Correa-Quezada et al [59] clarified that these industries have a significant influence on local/regional development.…”
Section: Creativity In Citiesmentioning
confidence: 99%
“…The fact of adopting this feature for development assessment is confirmed by the studies described e.g. in the works of Correa-Quezada et al (2018, pp. 1648-1649, Kohn &Wewel (2018, pp.…”
Section: Research Results and Discussionmentioning
confidence: 64%
“…Thus defined, they would seem to have made a substantial contribution in recent times to economic and urban development and now provide a new area of competitiveness for territories. An excellent review of what contribution creativity makes to the economy may be found in the works of Correa-Quezada et al [2] and Rodrigues and Franco [3]. Creative potential has also triggered a new competitiveness profile for regions and cities.…”
Section: Introductionmentioning
confidence: 99%
“…The latter, which appeared later, and which is the so-called occupational approach, is essentially based on Richard Florida's work [10] addressing the concept of the creative class, a group of professionals dedicated to activities related to more stylised cultural creation but that also embraces all of those specialising in designing and forging creative activities geared towards the market and that display a certain level of talent and skill and who tend to concentrate in specific areas that exhibit certain conditions and lifestyles [11]. There is also the stream that has given rise to numerous studies aimed at measuring the scale of the territorial agglomeration of creative classes, which is generally measured through the employment variable in creative occupations [2,12,13]. Based on the two approaches, many works have appeared that strive to develop a theoretical framework explaining the link between creativity and economic development [14,15] and to show how creativity can shape an area's competitive advantage [5,16], and which also provide ample margin to design and implement new regional policies [3,17].…”
Section: Introductionmentioning
confidence: 99%